2003
DOI: 10.1021/jp034804n
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation and Other Non-radiative Relaxation Processes in Gas-Phase Metal−DNA Base Complexes

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A previous experimental/theoretical work devoted to the determination of the neutral aluminum effect on the photochemistry of guanine cannot be considered useful for a comparison because the neutral atom and ion behave differently.…”
Section: Resultsmentioning
confidence: 99%
“…A previous experimental/theoretical work devoted to the determination of the neutral aluminum effect on the photochemistry of guanine cannot be considered useful for a comparison because the neutral atom and ion behave differently.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 For nucleobase complexes with neutral metal atoms, Pedersen and co-workers measured photoionization efficiency (PIE) spectra of Al-cytosine and Alguanine-(NH 3 ) 0-2 and studied photoinduced dehydrogenation of Al-L (L ) cytosine, guanine, and guanine-cytosine). [18][19][20] In these studies, the authors observed that the photophysics of the gas-phase complexes was similar to that of solution-phase bases.…”
Section: Introductionmentioning
confidence: 92%
“…Rodgers and Armentrout studied threshold collision-induced dissociation of M + L (M + = Li + , Na + , and K + ; L = uracil, thymine, and adenine) and M + (adenine) (M = Sc + , Ti + , V + , Cr + , Mn + , Fe + , Co + , Ni + , Cu + , and Zn + ) using guided ion beam mass spectrometry. , In combination with theoretical calculations, they examined the preferred binding sites of alkali, early transition, and late transition elements. Following these studies, Yang and Rodgers studied the threshold collision-induced dissociation of alkali ion complexes with substituted uracils and found that methalation, halogenation, thio substitution, or combination of these effects did not influence binding energies significantly or change the binding sites of the alkali ions. Using laser photodissociation, Yang and co-workers measured photofragmentation spectra of Mg + −L (L = uracil, thymine, and cytosine) and detected the dissociation products of the metal ion and organic fragments. , For nucleobase complexes with neutral metal atoms, Pedersen and co-workers measured photoionization efficiency (PIE) spectra of Al−cytosine and Al−guanine−(NH 3 ) 0 - 2 and studied photoinduced dehydrogenation of Al−L (L = cytosine, guanine, and guanine−cytosine). In these studies, the authors observed that the photophysics of the gas-phase complexes was similar to that of solution-phase bases.…”
Section: Introductionmentioning
confidence: 99%
“…17 Pederson et al investigated the photoinduced dehydrogenation processes in the Al-cytosine, Al-guanine, and Mn-guanine complexes. [18][19][20] Liu et al and Sun et al studied the photodissociation of Mg + -uracil, Mg +thymine, and Mg + -cytosine complexes and found that the site of bond rupture is at the carbonyl group bound to Mg + . 21,22 Gillis et al studied the structures of hydrated Li +cytosine and Li + -thymine complexes with infrared multiple photon dissociation and showed that the Li + ion bonds to the O 4 site in both cytosine and thymine.…”
Section: Introductionmentioning
confidence: 99%